THE EFFECT OF NOTCHES ON THE FATIGUE LIFE OF A NICKEL-BASE GAS TURBINE DISK MATERIAL - Robert Eriksson; Johan Moverare; Zhe Chen; Kjell Simonsson (Acta Polytechnica CTU Proceedings)
Gas turbine disks carry significant load under high temperatures and may be subject to fatigue failure. Disks contain several notches in the form of the fir tree blade attachments. Low cycle fatigue tests were performed on blunt notch compact tension specimens made from alloy 718. The results indicated that notch support needed to be incorporated not to cause an overly conservative life prediction. The notch support diminished as the plastic strain range decreased, indicating that notch support is only present in the low cycle fatigue regime. A critical distance approach was applied to account for the notch support. An equation relating the critical distance to the notch root stress was derived. The chosen life model was formulated in terms of a variation on the Smith–Watson–Topper (SWT) parameter. The modified SWT parameter taken at the critical distance was used in a life model calibrated for smooth specimens to successfully predict the fatigue life of notched specimens.